Sketch for a financial theory of the poem. Issue 6 (3rd June 2022) - Luna, Joe
ABSTRACT: This paper claims that there is such a thing as poetry that is sensitive to the capitalist logics of financial abstraction. It does this by situating poetry from the eighteenth and twenty-first centuries in relation to historically comparable revolutions in finance and financial instruments. It argues that such poetry offers ways in which to apprehend and materialise historical and contemporary financial abstraction; it further claims that such work signals and responds to the ways in which finance influences the relationship between social life and knowledge, in poems that interface the production of knowledge with capital's relentless chasing after value. In different ways and from different motivations, the work of Jonathan Swift and William Fuller leverages aesthetic form against the abstractive mechanisms of financialization and acts as a counterbalance against them. For Swift, this means the Tory humanist satire of credit and banking in the wake of the English Financial Revolution (and especially in the context of England's first great financial crisis, the so-called South Sea Bubble of 1720); for Fuller, this means his poetry's syntactical animation, and lyrical transcendence, of the formal logics of the derivative, the most profoundly transformative financial form of modern capitalism.